Feasibility of tumour-focused adaptive radiotherapy for bladder cancer on the MR-linac. (July 2022) - Mitchell, A.; Ingle, M.; Smith, G.; Chick, J.; Diamantopoulos, S.; Goodwin, E.; Herbert, T.; Huddart, R.; McNair, H.; Oelfke, U.; Nill, S.; Dunlop, A.; et al.
Highlights: Bladder tumour-focused magnetic resonance image-guided adaptive radiotherapy is feasible. We present an online adaptive workflow solution that is achievable in 30 min on a 1.5 T MR-linac. Target coverage is successfully maintained despite intra-fraction bladder filling. Abstract: Bladder tumour-focused magnetic resonance image-guided adaptive radiotherapy using a 1.5 Tesla MR-linac is feasible. A full online workflow adapting to anatomy at each fraction is achievable in approximately 30 min. Intra-fraction bladder filling did not compromise target coverage with the class solution employed.